Gender and Working Sector Comparisons in Personal Financial Planning - Ratna Khuzaimah, Mohamad (2010)
This research is being conducted in order to look into gender and working sector comparisons in personal financial planning due to the fact that by having personal financial planning it can help to lessen financial difficulties. The research examines whether there are differences between gender and working sectors with regard to financial literacy, attitudes to personal financial planning, and frequency in managing personal financial. For the purpose of this research, five items were included under personal financial planning, which are savings management, credit management, investment planning, insurance planning, and retirement planning. Data were collected through questionnaires distributed to the academic and non-academic staff in public and private institutions of higher learning. Results show that there are significant differences in financial literacy between gender and working sector comparisons, but not in attitudes towards personal financial planning. Results for frequency of managing personal financial planning show a significance difference between male and female staff,but no significant difference between the public and private sectors.